Exploring microstructure and texture evolution in AZX311 Mg alloy under cyclic shear deformation - Mahesh Panchal; Lalit Kaushik; Ravi Kottan Renganayagalu; Shi-Hoon Choi; Jaiveer Singh (Journal of Magnesium and Alloys)
The current study focuses on investigating the effect of in-plane cyclic shear (IPCS) on the microstructure and texture evolution in an AZX311 Mg alloy sheet using a customized in-plane shear jig. Samples were deformed at two distinct strain levels of 0.05 and 0.10, with tests conducted over different numbers of deformation cycles at each strain level. A detailed microstructural investigation using electron backscatter diffraction (EBSD) revealed that in-plane cyclic shear induced the formation of numerous tensile twins (TTWs) in the alloy sheet. Both the shear strain and the number of deformation cycles contributed to an increase in the twin volume fraction (TVF), which played a critical role in texture evolution. Notably, unlike in-plane shear (IPS) deformation, where two satellite peaks appear in opposite quadrants, in-plane cyclic shear resulted in satellite peaks across all four quadrants of the pole figure. The evolution of texture components across all four quadrants arises from the load variations under forward and reverse loading during cyclic deformation. Thus, in-plane cyclic shear deformation can generate texture components along nearly all directions in the pole figures. Additionally, microstructural and microtextural analyses revealed that TTW is the dominant deformation mechanism, contributing to texture evolution. Furthermore, the resolved shear stress (RSS) analysis indicated that prismatic slip activity predominantly governs dislocation slip behavior.